Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy. - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D'Agaro, Pierlanfranco (J Clin Virol, 2015)
A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.